ACCUMULATION OF ALUMINIUM IN THE TISSUE OF GIANT FRESH WATER PRAWN (Macrobrachium rosenbergii de Man) EXPOSED TO ACIDIC WATER CONTAMINATED WITH ALUMINIUM SALT - Sri Redjeki (JOURNAL OF COASTAL DEVELOPMENT, 2003)
Aluminium is known as competitive trivalent and its occurance in an acidic environment causes ionic disturbances in aquatic invertebrates and crustaceans. An investigation was conducted to determine the accumulation of aluminium in the tissue of giant fresh water prawn (M. rosenbergii de Man) exposed to acidic water  (pH 5.0) and more alkaline media (pH 6.5) contaminated by aluminium salt (0.3 mg/l of nominal concentration of Al).  A static test with regular water exchange was employed during the experiment. The first moulting was recorded in all treatments at the first week of the investigation.  Normal moulting period, i.e. 6 – 8 days after the first moulting was observed in 55% of prawns in the media with normal pH (pH 6.5).  A longer period, more than 10 days, was needed by prawn in the media at pH 6.5 with 0.3-mg/l aluminium, pH 5.0 and at pH 5.0 with 0.3 mg/l aluminiun.  The third moulting was only recorded at prawn in media at pH 6.5.  The elevated aluminium in the acidic media caused the highest mortality rate and there was no mortality recorded at normal pH.  Most of the mortality was observed before and soon after moulting. The elevation of 0.3 mg/l aluminium in the more acidic water (pH 5.0) increased the aluminium and decreased the calcium concentrations in the prawn tissue. However, the magnesium in the prawn’s tissue showed its highest consentration at pH 5.0 with 0.3-mg/l aluminium. The decrease of calcium concentration in the prawn’s tissue was always followed by the increase of concentration of aluminium significantly (P < 0.01).  This suggests that the aluminium interfers the intake of calcium from the media by the prawn.  However the magnesium intake was not affected.  As a conclusion, the elevated level of aluminium in the acidic media increased the accumulation of aluminium in the prawn’s tissue and influenced the moulting behaviour of the tested prawn by interfering the absortion of calsium and magnesium, i.e. decreasing the calcium and increasing the magnesium concentrations in the prawn tissue.